Exploring Vascular Function Biomarkers: Implications for Rehabilitation - Phillips,Shane A. (2017)
Abstract The endothelium plays an important role in maintaining vascular homeostasis and regulating blood vessel function. Endothelial function is considered an independent predictor for risk of future cardiovascular events in cardiovascular and non-cardiovascular patients, as well as a predictor for postoperative complications in cardiovascular surgery patients. Brachial artery flow-mediated dilation by high-resolution ultrasound is widely used to evaluate endothelium-dependent vasodilation, which is mainly mediated by nitric oxide release. Physical exercise exerts beneficial effects on endothelial function and can be used in both primary and secondary prevention of cardiac and peripheral artery diseases, even in the postoperative period of cardiovascular surgery.